Advanced steam measurement techniques: a study of how electrical capacitance measurements are affected by the spatial positioning of water within wet steam - Walker, David (2019)
This thesis gives an overview of the progress and difficulties in developing a better understanding of the effect of spatial positioning of the water phase on the Electrical Capacitance Tomography (ECT) measurement within a water steam mixture, and if this effect is different for an air water mixture. A novel experiment was proposed and conducted to test the effect of spatial positioning on the ECT measurement, by using a specially designed test rig that allowed for single or multiple droplets to be injected into controlled regions of the diameter of the sensor filled with static dry steam. In order to control the amount of water injected, an extensive study was conducted to predict and measure the size of droplets injected from different nozzles. The result of this gave rise to a novel way of modifying the Camsizer, to measure individual water droplets instead of dry particles, thus allowing for a droplet diameter measurement system that is able to photograph droplets. Further research was conducted with the measured droplets that theoretically predicted they would be able to survive being dropped through a dry steam environment. The spatial positioning testing was initially conducted with seven droplets being injected together into air and steam. This gave evidence that the measurement behaviour of water air and water steam mixtures are different for adjacent electrode pairs, by the water steam mixture being more susceptible to spatial positioning of the water phase. The behaviour is similar for opposite electrode pairs, although they were shown to not be susceptible to spatial positioning. To further improve the accuracy, the testing moved onto single droplet injections in steam. These results showed that opposite electrode pairs are not susceptible to spatial positioning. When the maximum recorded change in relative permittivity was compared to the parallel and droplet models of the permittivity of two phase flows, it was shown that the parallel model better predicted the results. This effect has also been observed previously within the literature on the work on wet steam. By modifying a flat plate capacitance model to measure the capacitance between curved electrodes in three dimensions, a novel 3D capacitance calculation program was developed for a four electrode electrical capacitance tomography system, in which to try to predict the measured results. The program was able to convert capacitances calculated to relative permittivity, and was shown to predict them with a difference of 0.18% to the parallel model. However when compared to the measured data for single droplets there was poor correlation. A program was also built to generate low spatial resolution images of cross sections of the water steam mix within the sensor within the injection time. The results from these images showed that the reconstruction was able to locate the correct region of droplet injection.